Pemberdayaan Masyarakat Melalui Inovasi Es Krim Kulit Pisang di Desa Andir - Egista Ratriningtyas; Hera Deva Marcita; Macharany Agustini Wahyudin; Nadia Bella Anggraini; Artisa, Rike Anggun (Politeknik STIA LAN Bandung, 2024)
This community service aims to explore the potential and innovation of using banana peels as well as an effort to empower the community. Banana peels are generally just thrown away so that the resulting banana peel waste increases and accumulates. In fact, banana peels contain nutrients that are very beneficial for the body. By reusing banana peel waste through processing it into ice cream, it can provide novelty and added value to society. This community empowerment activity is carried out by conducting outreach to the community through providing material regarding the benefits of banana peels and the practice of making banana peel ice cream directly with the community. This activity was carried out in Andir Village, Baleendah District, Bandung Regency, West Java, on December 10 2023. Through this community empowerment activity it can have an impact on economic growth because it creates business opportunities for the community, overcomes problems related to banana peel waste, and grows potential village.